Zur Entwicklung tiefenpsychologischer Ausbildungsinstitute: Das Beispiel des Heidelberger Instituts für Psychotherapie = Development of psychodynamic training institutes : Example of the Heidelberg Institute for Psychotherapy - Schauenburg, Henning; Dinger, Ulrike; Kriebel, Achim; Huber, Julia; Friederich, Hans-Christoph; Herzog, Wolfgang; Nikendei, Christoph (Psychotherapeut, 2019)
BackgroundThe changes in the psychotherapeutic landscape also place new demands on psychodynamic training institutes. These include the establishment of modern forms of teaching and supervision as well as participation in research activities, be it for the development of psychotherapeutic competencies or for process and effectiveness research.AimThis article describes the historical and institutional development of the Heidelberg Institute for Psychotherapy (HIP, founded in 2010), which, as a psychodynamic training institute close to the university, tries to do justice to the tasks mentioned above.Material and methodsThe structure, curricular structure and financing model as well as the development of research structures are presented.ConclusionThe activities of the HIP are successful in every respect and show that diversity in the field of psychotherapy (training) is feasible and in demand.